Cognitive complaints and cognitive impairment in patients with chronic daily headache - V. A. Golovacheva; V. A. Parfenov; A. A. Golovacheva (Неврология, нейропсихиатрия, психосоматика, 2017)
Comorbidities in chronic daily headache (CDH) include emotional disorders (depression, anxiety), insomnia, and musculoskeletal pain at other sites. In CDH, the most common type is a subjective  (according to patients themselves) and/or objective (based on the  results of cognitive tests) reduction in cognitive functions, which can  be caused by emotional disorders, insomnia and/or brain diseases,  and a negative effect of chronic pain on cognitive functions.Objective: to analyze cognitive complaints and their changes in patients with CDH.Patients and methods. Subjective complaints and cognitive functions were evaluated in 90 patients (76 women and 14 men) aged 23 to 78 years (mean age, 46.7±12.0 years) with primary  forms of CDH according to the Montreal Cognitive Assessment (MCA) for 12 months. The majority (68.9%) of patients with CHD  complained of diminished memory; however, its mild disorders (25– 26 MCA scores) were found in only a small proportion (23.3%). All  patients with subjective diminished memory were ascertained to  have neurotic disorders (depression, anxiety disorder) and/or insomnia or a concurrence of mental disorder and insomnia.Results and discussion. All the patients received treatment options, including optimal pharmacotherapy for headache and concomitant diseases, an educational conversation, cognitive- behavioral therapy, and therapeutic exercises. In cognitive  impairment (CI), cognitive training was used and Ginkgo biloba  extract (EGb 761®) prescribed; in sleep disorders, sleep hygiene  rules were explained. Therapy declined the mean number of  headache days a month from 29.1±2.03 (at baseline) to 9.3±9.35  (at 12-month follow-up) (p=0.002); while the subjective complaints regressed in the majority of patients; mild MCA changes persisted only in 6.7% of the patients. Management tactics for CHD patients  having mild CI and cardiovascular risk factors and the use of EGb  761® to improve cognitive functions were considered.Conclusion. It has been ascertained that in many cases, CI is associated with emotional disorders and insomnia, as well as with pathophysiological mechanisms of chronic pain itself; CI in some  patients has a vascular origin. The use of combined treatment  programs can promptly and effectively reduce the frequency of  headache and improve cognitive functions. EGb 761® (Tanakan®) has a beneficial effect on subjective CI and mild CI.